Genome editing of human embryos for research purposes: Japanese lay and expert attitudes - Akatsuka, Kyoko; Hatta, Taichi; Sawai, Tsutomu; Fujita, Misao (Frontiers in Genetics, 2023)
Background: Multiple surveys of the general public and experts on human genome editing have been conducted. However, many focused only on editing in clinical applications, with few regarding its use for basic research. Given that genome editing for research purposes is indispensable for the realization of clinical genome editing, understanding lay attitudes toward genome editing in research, particularly using human embryos, which is likely to provoke ethical concerns, is helpful for future societal discussion. Methods: An online survey was conducted with Japanese laypeople and researchers to ascertain their views regarding human genome editing for research purposes. Participants were queried about their acceptance as a function of the target of genome editing (germ cells, surplus IVF embryos, research embryos, somatic cells); then, those who answered “acceptable depending on the purpose” were asked about their acceptance in the context of specific research purposes of genome editing. Participants were also asked about their expectations and concerns regarding human genome editing. Results: Replies were obtained from 4,424 laypeople and 98 researchers. Approximately 28.2−36.9% of the laypeople exhibited strong resistance to genome editing for research purposes regardless of their applications. In contrast, 25.5% of the researchers demonstrated resistance only to genome editing in research embryos; this percentage was substantially higher than those concerning the other three targets (5.1−9.2%). Approximately 50.4−63.4% of laypeople who answered “acceptable depending on the purpose” approved germline genome editing for disease research; however, only 39.3−42.8% approved genome editing in basic research to obtain biological knowledge. In contrast, the researchers displayed a lower degree of acceptance of germline genome editing for research purposes related to chronic diseases (60.9−66.7%) than for other research purposes (73.6−90.8%). Analysis of responses concerning expectations and concerns indicated that laypeople who would not accept genome editing of human embryos did not necessarily worry about “instrumentalization of the embryo.” They also had substantially low expectations for recognized advantages of genome editing, including “advances in science” and “reduction of intractable diseases,” compared with other groups of respondents. Conclusion: The assumptions shared among experts in conventional bioethical debates and policy discussions on human genome editing are not self-evident to laypeople.